2019
DOI: 10.5398/tasj.2019.42.2.152
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical, Microbiology, and Sensory Characteristics of Kefir Goat Milk with Different Levels of Kefir Grain

Abstract: Kefir is a fermented milk product. The kefir grain starter consists of lactic acid bacteria and yeast that produce lactic acid and alcohol. The quality of kefir is strongly influenced by the type of milk used, the amount of kefir grain, kefir grain microorganisms, and the incubation period. The characteristics of goat-milk kefir with the addition of different amounts of kefir grain were studied by measuring pH value, ethanol content, and percentage of lactic acid. The experimental design was a completely rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 19 publications
1
11
1
3
Order By: Relevance
“…Furthermore, the results obtained in this work show that all of the analyzed parameters (main fermentative characteristics, aromatic profile, and sensory evaluation) are expressed in a balanced way when fermentation is carried out by the yeast consortium. In particular, the results showed that the yeast consortium had a significant effect on higher alcohols in all milks tested, in accordance with Sulmiyati et al [44]. In particular, acetaldehyde levels were always increased after consortium fermentation, in line with those reported by Grønnevik et al [22].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the results obtained in this work show that all of the analyzed parameters (main fermentative characteristics, aromatic profile, and sensory evaluation) are expressed in a balanced way when fermentation is carried out by the yeast consortium. In particular, the results showed that the yeast consortium had a significant effect on higher alcohols in all milks tested, in accordance with Sulmiyati et al [44]. In particular, acetaldehyde levels were always increased after consortium fermentation, in line with those reported by Grønnevik et al [22].…”
Section: Discussionsupporting
confidence: 90%
“…The sensory evaluation was conducted to evaluate whether the addition of green tea powder affected the sensory characteristics of lamb sausages. The sensory evaluation used in this study was a qualitative test with structured questionnaire protocol that was developed according to Sulmiyati et al (2019) with a modification. A 15 well-trained students and laboratory staff (aged between 24-30 years) who were familiar with sausage sensory evaluation were recruited to evaluate 5 sausage samples.…”
Section: Sensory Characteristics Evaluationmentioning
confidence: 99%
“…Laktosa sebagai sumber karbohidrat utama dalam susu digunakan dalam proses fermentasi kefir oleh bakteri asam laktat. Penggunaan bibit kefir yang semakin banyak akan semakin menurunkan kadar laktosa dalam susu (Setyawardani et al, 2017;Sulmiyati et al, 2019). Tomar et al (2019).…”
Section: Hasil Dan Pembahasan Pengaruh Jenis Susu Terhadap Kandungan ...unclassified
“…Khamir selanjutnya akan menghasilkan senyawasenyawa yang membantu pertumbuhan bakteri asam laktat seperti asam amino dan vitamin. Khamir juga dapat menghasilkan senyawa metabolit berupa CO2 yang dapat membantu memberikan lingkungan yang anaerobik serta mencegah akumulasi asam laktat yang berlebihan sehingga dapat memperpanjang pertumbuhan bakteri asam laktat (Setiawati dan Yunianta, 2018;Korukluoglu et al, 2017;Setyawardani et al, 2017) Hasil nilai pH kefir susu kambing yang tinggi pada penelitian Sulmiyati et al (2019), dikarenakan waktu fermentasinya lebih singkat yaitu 12 jam bila dibandingkan dengan waktu yang umumnya digunakan dalam pembuatan kefir yaitu 18-30 jam (Barão et al, 2019). Hal ini sejalan dengan penelitian yang dilakukan Kinteki et al (2018) yang meneliti pengaruh lama fermentasi pada kefir susu kambing.…”
Section: Tabel 1 Pengaruh Jenis Susu Terhadap Kandungan Protein Dan L...unclassified